Effectiveness of Financial Risk Management Implementation through Derivative Instruments at PT. Telekomunikasi Indonesia - Dian Safitri (Journal of Principles Management and Business, 2026)
This study examines the effectiveness of financial risk management through derivative instruments in a large emerging market corporation. As Indonesia’s leading telecommunications company, PT Telekomunikasi Indonesia Tbk is exposed to significant foreign exchange and interest rate risks due to its international operations and financing activities. This study aims to evaluate the extent to which derivative instruments contribute to mitigating these risks and enhancing financial stability. A qualitative descriptive approach with a case study method is employed, using secondary data from consolidated financial statements, annual reports, and risk management disclosures over the period 2018-2024. The analysis focuses on the use of forward contracts, interest rate swaps, and options within the company’s risk management framework. The findings indicate that derivative-based hedging strategies effectively reduce foreign exchange volatility, stabilize interest expenses, and improve financial performance indicators, particularly liquidity and leverage ratios. Furthermore, the integration of derivatives within an Enterprise Risk Management (ERM) framework enhances financial predictability and organizational resilience. This study provides practical implications for corporations operating in volatile financial environments, emphasizing the importance of structured hedging policies, strong risk governance, and transparent reporting. Academically, it contributes to the literature on financial risk management in emerging markets by offering empirical evidence on the long-term effectiveness of derivative instruments in non-financial corporations.